31.7: Difference between revisions

From testwiki
Jump to navigation Jump to search
 
 
Line 14: Line 14:
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
|-  
|-  
| [https://dlmf.nist.gov/31.7.E1 31.7.E1] || [[Item:Q9024|<math>\genhyperF{2}{1}@{\alpha,\beta}{\gamma}{z} = \HeunHl@{1}{\alpha\beta}{\alpha}{\beta}{\gamma}{\delta}{z}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\genhyperF{2}{1}@{\alpha,\beta}{\gamma}{z} = \HeunHl@{1}{\alpha\beta}{\alpha}{\beta}{\gamma}{\delta}{z}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>hypergeom([alpha , beta], [gamma], z) = HeunG(1, alpha*beta, alpha, beta, gamma, delta, z)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || Successful || Missing Macro Error || - || -
| [https://dlmf.nist.gov/31.7.E1 31.7.E1] || <math qid="Q9024">\genhyperF{2}{1}@{\alpha,\beta}{\gamma}{z} = \HeunHl@{1}{\alpha\beta}{\alpha}{\beta}{\gamma}{\delta}{z}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\genhyperF{2}{1}@{\alpha,\beta}{\gamma}{z} = \HeunHl@{1}{\alpha\beta}{\alpha}{\beta}{\gamma}{\delta}{z}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>hypergeom([alpha , beta], [gamma], z) = HeunG(1, alpha*beta, alpha, beta, gamma, delta, z)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || Successful || Missing Macro Error || - || -
|-  
|-  
| [https://dlmf.nist.gov/31.7.E1 31.7.E1] || [[Item:Q9024|<math>\HeunHl@{1}{\alpha\beta}{\alpha}{\beta}{\gamma}{\delta}{z} = \HeunHl@{0}{0}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\HeunHl@{1}{\alpha\beta}{\alpha}{\beta}{\gamma}{\delta}{z} = \HeunHl@{0}{0}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>HeunG(1, alpha*beta, alpha, beta, gamma, delta, z) = HeunG(0, 0, alpha, beta, gamma, alpha + beta + 1 - gamma, z)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || Successful || Missing Macro Error || - || -
| [https://dlmf.nist.gov/31.7.E1 31.7.E1] || <math qid="Q9024">\HeunHl@{1}{\alpha\beta}{\alpha}{\beta}{\gamma}{\delta}{z} = \HeunHl@{0}{0}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\HeunHl@{1}{\alpha\beta}{\alpha}{\beta}{\gamma}{\delta}{z} = \HeunHl@{0}{0}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>HeunG(1, alpha*beta, alpha, beta, gamma, delta, z) = HeunG(0, 0, alpha, beta, gamma, alpha + beta + 1 - gamma, z)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || Successful || Missing Macro Error || - || -
|-  
|-  
| [https://dlmf.nist.gov/31.7.E1 31.7.E1] || [[Item:Q9024|<math>\HeunHl@{0}{0}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z} = \HeunHl@{a}{a\alpha\beta}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\HeunHl@{0}{0}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z} = \HeunHl@{a}{a\alpha\beta}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>HeunG(0, 0, alpha, beta, gamma, alpha + beta + 1 - gamma, z) = HeunG(a, a*alpha*beta, alpha, beta, gamma, alpha + beta + 1 - gamma, z)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || Successful || Missing Macro Error || - || -
| [https://dlmf.nist.gov/31.7.E1 31.7.E1] || <math qid="Q9024">\HeunHl@{0}{0}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z} = \HeunHl@{a}{a\alpha\beta}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\HeunHl@{0}{0}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z} = \HeunHl@{a}{a\alpha\beta}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>HeunG(0, 0, alpha, beta, gamma, alpha + beta + 1 - gamma, z) = HeunG(a, a*alpha*beta, alpha, beta, gamma, alpha + beta + 1 - gamma, z)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || Successful || Missing Macro Error || - || -
|-  
|-  
| [https://dlmf.nist.gov/31.7.E2 31.7.E2] || [[Item:Q9025|<math>\HeunHl@{2}{\alpha\beta}{\alpha}{\beta}{\gamma}{\alpha+\beta-2\gamma+1}{z} = \genhyperF{2}{1}@{\tfrac{1}{2}\alpha,\tfrac{1}{2}\beta}{\gamma}{1-(1-z)^{2}}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\HeunHl@{2}{\alpha\beta}{\alpha}{\beta}{\gamma}{\alpha+\beta-2\gamma+1}{z} = \genhyperF{2}{1}@{\tfrac{1}{2}\alpha,\tfrac{1}{2}\beta}{\gamma}{1-(1-z)^{2}}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>HeunG(2, alpha*beta, alpha, beta, gamma, alpha + beta - 2*gamma + 1, z) = hypergeom([(1)/(2)*alpha ,(1)/(2)*beta], [gamma], 1 -(1 - z)^(2))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || Failure || Missing Macro Error || Successful [Tested: 90] || -
| [https://dlmf.nist.gov/31.7.E2 31.7.E2] || <math qid="Q9025">\HeunHl@{2}{\alpha\beta}{\alpha}{\beta}{\gamma}{\alpha+\beta-2\gamma+1}{z} = \genhyperF{2}{1}@{\tfrac{1}{2}\alpha,\tfrac{1}{2}\beta}{\gamma}{1-(1-z)^{2}}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\HeunHl@{2}{\alpha\beta}{\alpha}{\beta}{\gamma}{\alpha+\beta-2\gamma+1}{z} = \genhyperF{2}{1}@{\tfrac{1}{2}\alpha,\tfrac{1}{2}\beta}{\gamma}{1-(1-z)^{2}}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>HeunG(2, alpha*beta, alpha, beta, gamma, alpha + beta - 2*gamma + 1, z) = hypergeom([(1)/(2)*alpha ,(1)/(2)*beta], [gamma], 1 -(1 - z)^(2))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || Failure || Missing Macro Error || Successful [Tested: 90] || -
|-  
|-  
| [https://dlmf.nist.gov/31.7.E3 31.7.E3] || [[Item:Q9026|<math>\HeunHl@{4}{\alpha\beta}{\alpha}{\beta}{\tfrac{1}{2}}{\tfrac{2}{3}(\alpha+\beta)}{z} = \genhyperF{2}{1}@{\tfrac{1}{3}\alpha,\tfrac{1}{3}\beta}{\tfrac{1}{2}}{1-(1-z)^{2}(1-\tfrac{1}{4}z)}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\HeunHl@{4}{\alpha\beta}{\alpha}{\beta}{\tfrac{1}{2}}{\tfrac{2}{3}(\alpha+\beta)}{z} = \genhyperF{2}{1}@{\tfrac{1}{3}\alpha,\tfrac{1}{3}\beta}{\tfrac{1}{2}}{1-(1-z)^{2}(1-\tfrac{1}{4}z)}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>HeunG(4, alpha*beta, alpha, beta, (1)/(2), (2)/(3)*(alpha + beta), z) = hypergeom([(1)/(3)*alpha ,(1)/(3)*beta], [(1)/(2)], 1 -(1 - z)^(2)*(1 -(1)/(4)*z))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || Failure || Missing Macro Error || Successful [Tested: 9] || -
| [https://dlmf.nist.gov/31.7.E3 31.7.E3] || <math qid="Q9026">\HeunHl@{4}{\alpha\beta}{\alpha}{\beta}{\tfrac{1}{2}}{\tfrac{2}{3}(\alpha+\beta)}{z} = \genhyperF{2}{1}@{\tfrac{1}{3}\alpha,\tfrac{1}{3}\beta}{\tfrac{1}{2}}{1-(1-z)^{2}(1-\tfrac{1}{4}z)}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\HeunHl@{4}{\alpha\beta}{\alpha}{\beta}{\tfrac{1}{2}}{\tfrac{2}{3}(\alpha+\beta)}{z} = \genhyperF{2}{1}@{\tfrac{1}{3}\alpha,\tfrac{1}{3}\beta}{\tfrac{1}{2}}{1-(1-z)^{2}(1-\tfrac{1}{4}z)}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>HeunG(4, alpha*beta, alpha, beta, (1)/(2), (2)/(3)*(alpha + beta), z) = hypergeom([(1)/(3)*alpha ,(1)/(3)*beta], [(1)/(2)], 1 -(1 - z)^(2)*(1 -(1)/(4)*z))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || Failure || Missing Macro Error || Successful [Tested: 9] || -
|-  
|-  
| [https://dlmf.nist.gov/31.7.E4 31.7.E4] || [[Item:Q9027|<math>\HeunHl@{\tfrac{1}{2}+i\tfrac{\sqrt{3}}{2}}{\alpha\beta(\tfrac{1}{2}+i\tfrac{\sqrt{3}}{6})}{\alpha}{\beta}{\tfrac{1}{3}(\alpha+\beta+1)}{\tfrac{1}{3}(\alpha+\beta+1)}{z} = \genhyperF{2}{1}@{\tfrac{1}{3}\alpha,\tfrac{1}{3}\beta}{\tfrac{1}{3}(\alpha+\beta+1)}{1-\left(1-\left(\tfrac{3}{2}-i\tfrac{\sqrt{3}}{2}\right)z\right)^{3}}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\HeunHl@{\tfrac{1}{2}+i\tfrac{\sqrt{3}}{2}}{\alpha\beta(\tfrac{1}{2}+i\tfrac{\sqrt{3}}{6})}{\alpha}{\beta}{\tfrac{1}{3}(\alpha+\beta+1)}{\tfrac{1}{3}(\alpha+\beta+1)}{z} = \genhyperF{2}{1}@{\tfrac{1}{3}\alpha,\tfrac{1}{3}\beta}{\tfrac{1}{3}(\alpha+\beta+1)}{1-\left(1-\left(\tfrac{3}{2}-i\tfrac{\sqrt{3}}{2}\right)z\right)^{3}}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>HeunG((1)/(2)+ I*(sqrt(3))/(2), alpha*beta*((1)/(2)+ I*(sqrt(3))/(6)), alpha, beta, (1)/(3)*(alpha + beta + 1), (1)/(3)*(alpha + beta + 1), z) = hypergeom([(1)/(3)*alpha ,(1)/(3)*beta], [(1)/(3)*(alpha + beta + 1)], 1 -(1 -((3)/(2)- I*(sqrt(3))/(2))*z)^(3))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || Failure || Missing Macro Error || <div class="toccolours mw-collapsible mw-collapsed">Failed [9 / 9]<div class="mw-collapsible-content"><syntaxhighlight lang=mathematica>Result: 0.-.9402251684*I
| [https://dlmf.nist.gov/31.7.E4 31.7.E4] || <math qid="Q9027">\HeunHl@{\tfrac{1}{2}+i\tfrac{\sqrt{3}}{2}}{\alpha\beta(\tfrac{1}{2}+i\tfrac{\sqrt{3}}{6})}{\alpha}{\beta}{\tfrac{1}{3}(\alpha+\beta+1)}{\tfrac{1}{3}(\alpha+\beta+1)}{z} = \genhyperF{2}{1}@{\tfrac{1}{3}\alpha,\tfrac{1}{3}\beta}{\tfrac{1}{3}(\alpha+\beta+1)}{1-\left(1-\left(\tfrac{3}{2}-i\tfrac{\sqrt{3}}{2}\right)z\right)^{3}}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\HeunHl@{\tfrac{1}{2}+i\tfrac{\sqrt{3}}{2}}{\alpha\beta(\tfrac{1}{2}+i\tfrac{\sqrt{3}}{6})}{\alpha}{\beta}{\tfrac{1}{3}(\alpha+\beta+1)}{\tfrac{1}{3}(\alpha+\beta+1)}{z} = \genhyperF{2}{1}@{\tfrac{1}{3}\alpha,\tfrac{1}{3}\beta}{\tfrac{1}{3}(\alpha+\beta+1)}{1-\left(1-\left(\tfrac{3}{2}-i\tfrac{\sqrt{3}}{2}\right)z\right)^{3}}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>HeunG((1)/(2)+ I*(sqrt(3))/(2), alpha*beta*((1)/(2)+ I*(sqrt(3))/(6)), alpha, beta, (1)/(3)*(alpha + beta + 1), (1)/(3)*(alpha + beta + 1), z) = hypergeom([(1)/(3)*alpha ,(1)/(3)*beta], [(1)/(3)*(alpha + beta + 1)], 1 -(1 -((3)/(2)- I*(sqrt(3))/(2))*z)^(3))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || Failure || Missing Macro Error || <div class="toccolours mw-collapsible mw-collapsed">Failed [9 / 9]<div class="mw-collapsible-content"><syntaxhighlight lang=mathematica>Result: 0.-.9402251684*I
Test Values: {alpha = 3/2, beta = 3/2, z = 1/2}</syntaxhighlight><br><syntaxhighlight lang=mathematica>Result: 0.-.3436010475*I
Test Values: {alpha = 3/2, beta = 3/2, z = 1/2}</syntaxhighlight><br><syntaxhighlight lang=mathematica>Result: 0.-.3436010475*I
Test Values: {alpha = 3/2, beta = 1/2, z = 1/2}</syntaxhighlight><br>... skip entries to safe data</div></div> || -
Test Values: {alpha = 3/2, beta = 1/2, z = 1/2}</syntaxhighlight><br>... skip entries to safe data</div></div> || -
|}
|}
</div>
</div>

Latest revision as of 12:11, 28 June 2021


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
31.7.E1 F 1 2 ( α , β ; γ ; z ) = H ( 1 , α β ; α , β , γ , δ ; z ) Gauss-hypergeometric-F-as-2F1 𝛼 𝛽 𝛾 𝑧 Heun-local 1 𝛼 𝛽 𝛼 𝛽 𝛾 𝛿 𝑧 {\displaystyle{\displaystyle{{}_{2}F_{1}}\left(\alpha,\beta;\gamma;z\right)=% \mathit{H\!\ell}\left(1,\alpha\beta;\alpha,\beta,\gamma,\delta;z\right)}}
\genhyperF{2}{1}@{\alpha,\beta}{\gamma}{z} = \HeunHl@{1}{\alpha\beta}{\alpha}{\beta}{\gamma}{\delta}{z}
| z | < 1 𝑧 1 {\displaystyle{\displaystyle|z|<1}}
hypergeom([alpha , beta], [gamma], z) = HeunG(1, alpha*beta, alpha, beta, gamma, delta, z)
Error
Successful Missing Macro Error - -
31.7.E1 H ( 1 , α β ; α , β , γ , δ ; z ) = H ( 0 , 0 ; α , β , γ , α + β + 1 - γ ; z ) Heun-local 1 𝛼 𝛽 𝛼 𝛽 𝛾 𝛿 𝑧 Heun-local 0 0 𝛼 𝛽 𝛾 𝛼 𝛽 1 𝛾 𝑧 {\displaystyle{\displaystyle\mathit{H\!\ell}\left(1,\alpha\beta;\alpha,\beta,% \gamma,\delta;z\right)=\mathit{H\!\ell}\left(0,0;\alpha,\beta,\gamma,\alpha+% \beta+1-\gamma;z\right)}}
\HeunHl@{1}{\alpha\beta}{\alpha}{\beta}{\gamma}{\delta}{z} = \HeunHl@{0}{0}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z}
| z | < 1 𝑧 1 {\displaystyle{\displaystyle|z|<1}}
HeunG(1, alpha*beta, alpha, beta, gamma, delta, z) = HeunG(0, 0, alpha, beta, gamma, alpha + beta + 1 - gamma, z)
Error
Successful Missing Macro Error - -
31.7.E1 H ( 0 , 0 ; α , β , γ , α + β + 1 - γ ; z ) = H ( a , a α β ; α , β , γ , α + β + 1 - γ ; z ) Heun-local 0 0 𝛼 𝛽 𝛾 𝛼 𝛽 1 𝛾 𝑧 Heun-local 𝑎 𝑎 𝛼 𝛽 𝛼 𝛽 𝛾 𝛼 𝛽 1 𝛾 𝑧 {\displaystyle{\displaystyle\mathit{H\!\ell}\left(0,0;\alpha,\beta,\gamma,% \alpha+\beta+1-\gamma;z\right)=\mathit{H\!\ell}\left(a,a\alpha\beta;\alpha,% \beta,\gamma,\alpha+\beta+1-\gamma;z\right)}}
\HeunHl@{0}{0}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z} = \HeunHl@{a}{a\alpha\beta}{\alpha}{\beta}{\gamma}{\alpha+\beta+1-\gamma}{z}
| z | < 1 𝑧 1 {\displaystyle{\displaystyle|z|<1}}
HeunG(0, 0, alpha, beta, gamma, alpha + beta + 1 - gamma, z) = HeunG(a, a*alpha*beta, alpha, beta, gamma, alpha + beta + 1 - gamma, z)
Error
Successful Missing Macro Error - -
31.7.E2 H ( 2 , α β ; α , β , γ , α + β - 2 γ + 1 ; z ) = F 1 2 ( 1 2 α , 1 2 β ; γ ; 1 - ( 1 - z ) 2 ) Heun-local 2 𝛼 𝛽 𝛼 𝛽 𝛾 𝛼 𝛽 2 𝛾 1 𝑧 Gauss-hypergeometric-F-as-2F1 1 2 𝛼 1 2 𝛽 𝛾 1 superscript 1 𝑧 2 {\displaystyle{\displaystyle\mathit{H\!\ell}\left(2,\alpha\beta;\alpha,\beta,% \gamma,\alpha+\beta-2\gamma+1;z\right)={{}_{2}F_{1}}\left(\tfrac{1}{2}\alpha,% \tfrac{1}{2}\beta;\gamma;1-(1-z)^{2}\right)}}
\HeunHl@{2}{\alpha\beta}{\alpha}{\beta}{\gamma}{\alpha+\beta-2\gamma+1}{z} = \genhyperF{2}{1}@{\tfrac{1}{2}\alpha,\tfrac{1}{2}\beta}{\gamma}{1-(1-z)^{2}}
| z | < 1 𝑧 1 {\displaystyle{\displaystyle|z|<1}}
HeunG(2, alpha*beta, alpha, beta, gamma, alpha + beta - 2*gamma + 1, z) = hypergeom([(1)/(2)*alpha ,(1)/(2)*beta], [gamma], 1 -(1 - z)^(2))
Error
Failure Missing Macro Error Successful [Tested: 90] -
31.7.E3 H ( 4 , α β ; α , β , 1 2 , 2 3 ( α + β ) ; z ) = F 1 2 ( 1 3 α , 1 3 β ; 1 2 ; 1 - ( 1 - z ) 2 ( 1 - 1 4 z ) ) Heun-local 4 𝛼 𝛽 𝛼 𝛽 1 2 2 3 𝛼 𝛽 𝑧 Gauss-hypergeometric-F-as-2F1 1 3 𝛼 1 3 𝛽 1 2 1 superscript 1 𝑧 2 1 1 4 𝑧 {\displaystyle{\displaystyle\mathit{H\!\ell}\left(4,\alpha\beta;\alpha,\beta,% \tfrac{1}{2},\tfrac{2}{3}(\alpha+\beta);z\right)={{}_{2}F_{1}}\left(\tfrac{1}{% 3}\alpha,\tfrac{1}{3}\beta;\tfrac{1}{2};1-(1-z)^{2}(1-\tfrac{1}{4}z)\right)}}
\HeunHl@{4}{\alpha\beta}{\alpha}{\beta}{\tfrac{1}{2}}{\tfrac{2}{3}(\alpha+\beta)}{z} = \genhyperF{2}{1}@{\tfrac{1}{3}\alpha,\tfrac{1}{3}\beta}{\tfrac{1}{2}}{1-(1-z)^{2}(1-\tfrac{1}{4}z)}
| z | < 1 𝑧 1 {\displaystyle{\displaystyle|z|<1}}
HeunG(4, alpha*beta, alpha, beta, (1)/(2), (2)/(3)*(alpha + beta), z) = hypergeom([(1)/(3)*alpha ,(1)/(3)*beta], [(1)/(2)], 1 -(1 - z)^(2)*(1 -(1)/(4)*z))
Error
Failure Missing Macro Error Successful [Tested: 9] -
31.7.E4 H ( 1 2 + i 3 2 , α β ( 1 2 + i 3 6 ) ; α , β , 1 3 ( α + β + 1 ) , 1 3 ( α + β + 1 ) ; z ) = F 1 2 ( 1 3 α , 1 3 β ; 1 3 ( α + β + 1 ) ; 1 - ( 1 - ( 3 2 - i 3 2 ) z ) 3 ) Heun-local 1 2 𝑖 3 2 𝛼 𝛽 1 2 𝑖 3 6 𝛼 𝛽 1 3 𝛼 𝛽 1 1 3 𝛼 𝛽 1 𝑧 Gauss-hypergeometric-F-as-2F1 1 3 𝛼 1 3 𝛽 1 3 𝛼 𝛽 1 1 superscript 1 3 2 𝑖 3 2 𝑧 3 {\displaystyle{\displaystyle\mathit{H\!\ell}\left(\tfrac{1}{2}+i\tfrac{\sqrt{3% }}{2},\alpha\beta(\tfrac{1}{2}+i\tfrac{\sqrt{3}}{6});\alpha,\beta,\tfrac{1}{3}% (\alpha+\beta+1),\tfrac{1}{3}(\alpha+\beta+1);z\right)={{}_{2}F_{1}}\left(% \tfrac{1}{3}\alpha,\tfrac{1}{3}\beta;\tfrac{1}{3}(\alpha+\beta+1);1-\left(1-% \left(\tfrac{3}{2}-i\tfrac{\sqrt{3}}{2}\right)z\right)^{3}\right)}}
\HeunHl@{\tfrac{1}{2}+i\tfrac{\sqrt{3}}{2}}{\alpha\beta(\tfrac{1}{2}+i\tfrac{\sqrt{3}}{6})}{\alpha}{\beta}{\tfrac{1}{3}(\alpha+\beta+1)}{\tfrac{1}{3}(\alpha+\beta+1)}{z} = \genhyperF{2}{1}@{\tfrac{1}{3}\alpha,\tfrac{1}{3}\beta}{\tfrac{1}{3}(\alpha+\beta+1)}{1-\left(1-\left(\tfrac{3}{2}-i\tfrac{\sqrt{3}}{2}\right)z\right)^{3}}
| z | < 1 𝑧 1 {\displaystyle{\displaystyle|z|<1}}
HeunG((1)/(2)+ I*(sqrt(3))/(2), alpha*beta*((1)/(2)+ I*(sqrt(3))/(6)), alpha, beta, (1)/(3)*(alpha + beta + 1), (1)/(3)*(alpha + beta + 1), z) = hypergeom([(1)/(3)*alpha ,(1)/(3)*beta], [(1)/(3)*(alpha + beta + 1)], 1 -(1 -((3)/(2)- I*(sqrt(3))/(2))*z)^(3))
Error
Failure Missing Macro Error
Failed [9 / 9]
Result: 0.-.9402251684*I
Test Values: {alpha = 3/2, beta = 3/2, z = 1/2}

Result: 0.-.3436010475*I
Test Values: {alpha = 3/2, beta = 1/2, z = 1/2}

... skip entries to safe data
-